In vitro characterization of surface properties through living cells - Diesner, Mark-Oliver; Howell, Caitlin; Kurz, Volker L.; Verreault, Dominique; Kölsch, Patrick (The journal of physical chemistry letters, 2010)
The ability to probe an interface beneath a layer of living cells in situ without the need for labeling and fixation has the potential to unlock some of the key questions in cell biology and biointerfacial phenomena. Here, we show that vibrational sum frequency generation (SFG) spectroscopy can be used to detect alkanethiol self-assembled monolayers (SAMs) buried underneath a layer of living erythrocytes (ECs). SFG spectra with and without ECs showed the spectral signatures typical of these SAMs, indicating that the signal was being generated solely by the SAM and was not influenced by the presence of cells. Direct comparison of infrared spectroscopy to SFG measurements of cells adhered on a fibronectin layer showed that the SFG signal emanated solely from this layer. These results have important implications for the characterization of surfaces in biomedical, environmental, and industrial applications.
Gesehen am 02.02.2023